2016
DOI: 10.1111/bcpt.12634
|View full text |Cite
|
Sign up to set email alerts
|

Do Diuretics have Antinociceptive Actions: Studies of Spironolactone, Eplerenone, Furosemide and Chlorothiazide, Individually and with Oxycodone and Morphine

Abstract: Spironolactone, eplerenone, chlorothiazide and furosemide are diuretics that have been suggested to have antinociceptive properties, for example via mineralocorticoid receptor antagonism. In co-administration, diuretics might enhance the antinociceptive effect of opioids via pharmacodynamic and pharmacokinetic mechanisms. Effects of spironolactone (100 mg/kg, i.p.), eplerenone (100 mg/kg, i.p.), chlorothiazide (50 mg/kg, i.p.) and furosemide (100 mg/kg, i.p.) were studied on acute oxycodone (0.75 mg/kg, s.c.)-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 27 publications
3
5
0
Order By: Relevance
“…The former is often used to investigate the analgesic activity of a drug, which is probably achieved through its effect on central the nervous system (34). Using this test, the present study verified that combined administration of nefopam and acetaminophen has potential as a viable novel therapy for pain.…”
Section: Discussionsupporting
confidence: 69%
“…The former is often used to investigate the analgesic activity of a drug, which is probably achieved through its effect on central the nervous system (34). Using this test, the present study verified that combined administration of nefopam and acetaminophen has potential as a viable novel therapy for pain.…”
Section: Discussionsupporting
confidence: 69%
“…Although the corticosterone inactivating enzyme 11ßHSD2 colocalized with sensory neuron MR allows MR activation predominantly by aldosterone [8], the co-activation by corticosterone cannot be fully excluded. Our findings are in agreement with older studies which have shown a long-lasting analgesic effect of MR antagonists [27,28].…”
Section: Discussionsupporting
confidence: 94%
“…Consequently, this FAD286mediated aldosterone reduction during FCA hindpaw inflammation not only reversed the enhanced expression of the pain signaling molecules TRPV1, CGRP, Nav1.8, and trkA, but also attenuated nociceptive behavior. Our findings of a transcriptional regulation of pain signaling molecules and subsequent nociceptive behavior are consistent with older studies [27,28] which showed a longlasting analgesic effect of MR antagonists.…”
Section: Discussionsupporting
confidence: 92%
“…When the span of time is more than 10 s, it is recommended to quickly remove the mouse's tail from hot water to avoid injury to the mice. The longer span of time in the tail flick test reveals the better antinociceptive effect of the treatment [36][37][38].…”
Section: Tail Flick Test (Antinociceptive Behavioral Evaluation)mentioning
confidence: 96%